O EMPREGO DO MODELO PEDAGOGICO BALANCEADO NO PROGRAMA DE GESTÃO DO CONHECIMENTO: UM ESTUDO DE CASO. - Guimarâes, José Carlos de Moraes (2008)
The pedagogic models widely studied under the scope of traditional Pedagogy are, unquestionably, the principal knowledge transmition channels, facilitating learning, contents memory retention, capacitating, and student habilitation, because they help and propitiate knowledge acquisition, and also support on teacher s action foundation. The present study on its scope intends to measure that the use of a balanced pedagogic model built among two theories - Jean Piaget s constructivist, where are defined interaction, assimilation, and accommodation concepts; and Nonaka and Takeuchi s knowledge creation in enterprise which evocates the knowledge spiral in socialization, externalization, combination, and interiorization levels may help the teacher to mediate teaching and learning within organizations scenario and, whit it, develop capabilities and skills peculiar of the entrepreneurship world. This proposal objectives to contribute with actions and practical experiments that could be applied in order to improve planning of initiatives focused on Enterprise Pedagogy, serving as a tool to support capacitating, maintenance, forming, and creation of intellectual capital programs, and also stimulate knowledge exchanges within corporative sphere